Gas sensor array based on tin oxide nano structure for VOCs detection - Thai, Nguyen Xuan; Duy, Nguyen Van; Hoa, Nguyen Duc; Hung, Chu Manh; Nguyen, Hugo; Hieu, Nguyen Van (Vietnam Journal of Science and Technology, 2020)
The detection of volatile organic compounds (VOCs) is very important in practical application in breath analysis. Thus, gas sensors based on metal oxide have been fabricated, but they lacked selectivity. One approach to resolve this task is to use array of highly sensitive and selective sensors as an electronic nose. Here we present a gas sensor array of Tin oxide nano-structure use of temperature modulation techniques. A Platinum micro-heater is accompanied with the array gas sensor. The gas sensor array was composing of five single sensors and that single sensor is located at different site from the micro heater and work at different temperatures. The gas sensing properties of the gas array sensors was investigated with VOC gases such as Ethanol, Methanol, Iso-propanol, and Acetone as well as NH3, H2, and H2S. We also confirm the good selectivity of the array sensor for Ethanol, Methanol, Iso-propanol, Acetone, NH3, H2, and H2S by using radar graphic method.